2006
DOI: 10.4049/jimmunol.176.3.1784
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Positive Cellular and Humoral Immune Responses by a Prime-Boost Vaccine Encoded with Simian Immunodeficiency Virusgag/pol

Abstract: It is believed likely that immune responses are responsible for controlling viral load and infection. In this study, when macaques were primed with plasmid DNA encoding SIV gag and pol genes (SIVgag/pol DNA) and then boosted with replication-deficient vaccinia virus DIs recombinant expressing the same genes (rDIsSIVgag/pol), this prime-boost regimen generated higher levels of Gag-specific CD4+ and CD8+ T cell responses than did either SIVgag/pol DNA or rDIsSIVgag/pol alone. When the macaques were i.v. challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…In brief, plasma samples were serially diluted and incubated with 100 TCID 50 s of challenge virus, and M8166 cells were then incubated as previously described (26). The neutralization was expressed as the percent inhibition of simian immunodeficiency virus p27 antigen production in the culture supernatants (38,39). Normal monkey plasma was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, plasma samples were serially diluted and incubated with 100 TCID 50 s of challenge virus, and M8166 cells were then incubated as previously described (26). The neutralization was expressed as the percent inhibition of simian immunodeficiency virus p27 antigen production in the culture supernatants (38,39). Normal monkey plasma was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo depletion studies with an anti-CD8 monoclonal antibody demonstrated that CD8 + cells are directly involved in containing simian immunodeficiency virus (SIV) infection in primates [11,12]. As such, the most promising and effective vaccine candidates to date against simian-human immunodeficiency virus (SHIV) challenge of macaques have aimed at inducing strong cellular immune responses [13][14][15][16]. Many vaccine candidates currently in clinical trials are focused on inducing cellular immune responses, especially CD8 + cytotoxic T lymphocyte (CTL) responses [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant MVA-based vaccines are being developed for a variety of diseases including HIV/AIDS (14, 20, 21, 24), and various SIV vaccines utilize prime/boost regimens, including DNA/recombinant MVA with or without IL-2 (2, 5) and DNA/recombinant adenovirus (35,38). A prime/boost regimen with DNA/recombinant DIs has been shown to elicit positive immunity in mice and macaque models (39,41). Furthermore, although rDIsSIVgag/pol was not able to replicate in the mammalian cell lines HeLa and CV-1 cells, it formed small plaques similar to those formed by MVA/SIV239gag/pol.…”
Section: Discussionmentioning
confidence: 99%
“…Because the vaccinia DIs strain lends itself to recombination, it could also be used as a vector expressing foreign genes (15,41). Recently, the simian immunodeficiency virus (SIV) gag and pol gene-encoded recombinant DIs (rDIsSIVgag/pol) proved effective at eliciting anti-SIV immunity in mice and macaques when administered as a booster antigen after priming with SIV-DNA (39,41) and with rBCGSIVgag (3).…”
mentioning
confidence: 99%